Hukuman Mati: Dari Tradisi Arab Menuju Hukum Al-Qur'an - Dede Rodin (Islamica: Jurnal Studi Keislaman, 2015)
The death penalty is the most Islamic law get resistance in its implementation. This resistance appears among others as a result of the symbolic understanding on the death penalty without understanding what and why this punishment stipulated in the Qur?an. Therefore, this article intends to answer the fundamental questions; how the concept of the death penalty in the Qur?an. This article resulted that the death penalty is one model of inculturation of the Qur?an to the existing tradition, with a change of paradigm regarding moral values and a more humane law, among others: (1) the principle of enforcement, from the original law ?vengeance? (vendetta, lex talionis, tha?r) to ?reply in kind?; (2) The motive for murder, of which initially involves all kinds of murder -including war- be designed killing and hir?bah only; (3) The prosecution, of which the extended family into the nuclear family; (4) accountability, from the collective responsibility to individual responsibility.